Control of biofilm from single and multispecies bacteria associated with food spoilage using metabolite of Streptomyces sp. KP110 and Pseudomonas fluorescens JB 3B - Budhiarto Halim; Diana Elizabeth Waturangi; Adi Yulandi (Scientific Reports)
Abstract Food spoilage bacteria are responsible for food spoilage and often fabricate biofilms on various surfaces. Naturally, biofilms are constructed by multiple bacterial species. These biofilms are more difficult to control compared to single species biofilms. Effective multispecies biofilm treatments are necessary in the food industry. This research evaluated antibiofilm activities of Streptomyces sp. KP110 and Pseudomonas fluorescens JB 3B metabolites. Prior to this research, the two antibiofilm crude extracts had shown significant results against various single species biofilms, including Bacillus, Shewanella, Vibrio, etc. The crude extracts also showed quorum-quenching activities, further asserting the antibiofilm potential. This research further characterized these antibiofilm crude extracts against multispecies biofilms, as well as assessing the duration of biofilm formation inhibition. The food spoilage bacteria used in this study are Bacillus cereus, Bacillus subtilis, and Shewanella putrefaciens. Both crude extracts showed antibiofilm activities with better results against Gram-negative bacteria. The metabolites are also considered nontoxic, meaning they are potential candidates for industrial purposes. The dominant active compounds of Streptomyces sp. KP110 are ticlopidine and hexadecanoid acid, while Pseudomonas fluorescens JB 3B are phenol and indole.